Contamporary gardens from the end of the XX-th to the beginning of the XXI-st centuries: integration of the subject “Silhouette and Plasticity” - Zaykova, E Yu (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii︠a︡ agronomii︠a︡ i zhivotnovodstvo, 2015)
In the article problems of an art and sign assessment of quality of the surrounding landscape environment and objects of landscape architecture on the basis of the subject “Silhouette and Plasticity” are presented. Using of semantic signs in creation of identical model of space means of landscaping assumes integrity of an image of landscape object with decorative and art characteristics. The choice of spatial signs will be estimated on examples of contemporary gardens from the end of the XX-th to the beginning of the XXI-st of centuries. The presented research allows to offer evidence-based algorithm of step-by-step transformation of the urbanized territories and to use means of landscaping as a semantic image of a place. On the example of the dominating signs it is offered to estimate the possibility of creation of spaces with the set visual characteristics (the line, form, silhouette, plasticity, scale, an image) and on their basis to offer versions of design solutions of urban areas.